Zoning Identification of the Candidate for Mount Sanggabuana Nature Park, Karawang Regency - Ina Revayanti (Green Publisher Indonesia, 2024)
Located at an altitude of 1,291 meters above sea level, Mount Sanggabuana is located in the Sanggabuana Mountains area and is the only highland with tropical rainforest in Karawang Regency. The tropical rainforest of the Sanggabuana Mountains is one of the oxygen and water contributors to the Karawang community with high natural tourism potential. In 2020 the status of the Sanggabuana Mountains forest, which is a Limited Production Forest, is proposed to be changed to a Nature Conservation Area with National Park status. The structuring of facilities and infrastructure, which has not been optimized, can affect the ecological, aesthetic and social value of a natural tourism destination comprehensively. This research aims to identify the natural attraction zone of Mount Sanggabuana as a natural tourism area design that prioritizes sustainable aspects by adopting the concept of ecotourism. This research uses a descriptive method with a quantitative approach. The analysis used is overlap analysis (superimpose) through the GIS (Geographic Information System) program produces natural tourism park zones supporting the Mount Sanggabuana area as a National Park.